Determinants of nutritional knowledge, attitude, and practice among southwestern Iranian households: A community-based study. Issue 2 (June 2020) - Naghashpour, Mahshid; Mansouri, Samaneh; Vadizadeh, Ali; Cheraghian, Bahman; Fallahi, Reza; Vaziri, Fateme
Background: Malnutrition is generally due to a lack of nutritional information rather than food deficiency. Therefore, the current knowledge, attitudes, and practice (KAP) of the target audience should be evaluated to eliminate malnutrition. However, KAP varies across demographic status and socioeconomic status (SES). Aim: The associations of nutritional KAP with demographic and socioeconomic variables were evaluated among households living in urban and rural areas of southwestern Iran. Methods: A cross-sectional, population-based study was conducted on 842 household heads (492 urban and 350 rural) using a standardized NUTRIKAP Household Questionnaire. The data evaluating nutritional KAP as well as demographic and socioeconomic information were obtained using a multi-stage cluster sampling method. SES score was also computed. Results: Urban households had a higher level of nutritional knowledge ( p < 0.05) but a lower level of nutritional attitude ( p < 0.001) and practice ( p < 0.001) compared with the rural ones. Rural households with the poorest quintiles of SES were 0.4 times less likely to have good nutritional knowledge (adjusted odds ratio = 0.4, confidence interval: 0.2, 0.9; p < 0.05), compared with higher quintiles. Households with an over-60-years-old household head had significantly higher nutritional attitude ( p < 0.05) and practice ( p <0.01) scores than households with younger ones. Households with male household heads had a higher nutritional practice score compared with households with female ones. Conclusions: These results can indicate the role of demographic and socioeconomic determinants in KAP of Iranian households towards the principle of nutrition and can be effective in prioritizing the implementation of nutritional interventions including nutrition education for them.